2019
DOI: 10.1002/cche.10229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistant starch type 4 supplementation of bread on in vitro glycemic index value, bile acid‐binding capacity, and mineral bioavailability

Abstract: Background and objectives RS4 is an alternative dietary fiber source with some potential physiological benefits giving better quality end products. Common dietary fiber sources including bran usually have deteriorative effect on color, textural properties, and consumer acceptability of breads. This study was designed to investigate the effect of RS4 supplementation on the bread quality as well as mineral bioavailability, bile acid‐binding capacity, in vitro glycemic index. Findings Loaf volumes of the breads s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…TDF contents of the whole wheat bread samples were higher than the TDF contents of the corresponding whole wheat flour. This might be due to resistant starch (Type 3) formation (gelatinization and retrogradation) during bread production and cooling [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…TDF contents of the whole wheat bread samples were higher than the TDF contents of the corresponding whole wheat flour. This might be due to resistant starch (Type 3) formation (gelatinization and retrogradation) during bread production and cooling [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was an increase in the dietary fiber content of the bread with RS and the staling time of these bread was longer. [ 47 ] The effects of bread containing β‐glucan, RS, or both on the GI and glycemic load in healthy individuals were investigated. The GI and glycemic load of the bread containing RS, β‐glucan, or both were significantly lower than those of white bread.…”
Section: Physiological Effects Of Using Resistant Starch In Breadmentioning
confidence: 99%
“…[134] Given that RS is beneficial to decrease postprandial glycaemia, its incorporation in bread is a common strategy to develop products with low GI. Aribas et al [15] found the increased substitution of wheat flour with RS4 (phosphorylated cross-linked) enhanced the nutritional properties of bread by increasing the amount of total dietary fiber, bile acid-binding capacity, mineral bioavailability values and decreasing GI. Bile acid binding is one of the most important characteristics of dietary fiber.…”
Section: Breadmentioning
confidence: 99%
“…[14] RS has been incorporated in the formulations to make functional food products. [15][16][17] Higher levels of RS in food could reduce the glycemic index and retard starch digestibility. Glycemic index (GI) is an index of the increase in postprandial blood glucose, which is divided into three levels: low GI (≤55), medium GI (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69), and high GI (≥70).…”
Section: Introductionmentioning
confidence: 99%